Synthesis, Structural Aspects and Catalytic Performance of a Tetrahedral Cobalt Phosphonate Framework - Sen, Rupam
A new phosphonate-based metal organic framework has been synthesized. The structure determined by X-ray crystallography reveals that it has an interesting 8-ring channel 3D structure having the Co-2-dimers as the secondary building unit. Topological analysis shows that it has 10-c uninodal 3D net structure with the Schlafli symbol 3(15).4(22).5(8). The magnetic measurement reveals the tetrahedral coordinated Co-II ion. The compound is highly active towards epoxidation in the presence of air and IBA (isobutyraldehyde). It catalyses almost all types of olefinic substrates with equal efficiency. The compound is highly stable thermally (370 degrees C) and under the reaction conditions as well. After the reaction it can be recovered quite easily and can be used for further reaction without any loss of activity over several cycles.